Detection on pharyngeal wall floppiness in patients with nonstructural factor‐induced obstructive sleep apnea‐hypopnea syndrome: Difference in position detection. (23rd March 2018) - Lin, Zhiqiang; Jiang, Kanglun; Zhao, Lin; Li, Shuna; Shao, Shu; Qian, Wei; Tao, Zezhang
Abstract : Objectives/Hypothesis: To evaluate changes in pharyngeal wall floppiness (PWF) between patients with obstructive sleep apnea‐hypopnea syndrome induced by non–upper‐airway structural factors and normal subjects, as well as the clinical significance using acoustic pharyngealmetry technology. Study Design: Cohort study. Methods: The obstructive sleep apnea (OSA) group (n = 102) and the normal control group (n = 50) were identified using the Eccovision Acoustic Pharyngometer measuring instrument. The volume of the pharyngeal cavity in the sitting and supine positions during expiration and inspiration was recorded, respectively, and the PWF index in the sitting and supine positions was calculated for further statistical analysis. Results: PWF in the sitting ( P  < .001) and supine positions ( P  < .001) in the OSA group was notably higher than that in the control group. PWF in the supine position in both the OSA group and control group was remarkably higher than that in the sitting position ( P  < .001, P  = .025, respectively). The difference in PWF between the supine and sitting positions (ΔPWF) (PWF_supine−PWF_sit) was distinctly higher than in control group ( P  < .01). PWF was positively correlated with age ( P  < .001) but not with body mass index ( P  > .05). Conclusions: PWF, quantified as elevated PWF, is an important nonstructural factor for the pathogenesis of OSA patients. PWF in the supine position can more accurately reflect airway collapsibility in OSA patients. Our pilot study of a novel observation may help us in the choice of proper surgical candidates for OSA procedures. Level of Evidence: 3b Laryngoscope, 128:2200–2205, 2018